ANALISIS POTENSI PAJAK PENERANGAN JALAN TERHADAP REALISASI PENERIMAAN PAJAK PENERANGAN JALAN DI KOTA SURAKARTA TAHUN 2011 – 2015 - Fadjar Harimurti, Abdul Ghofar, Suharno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
Taxes street lighting in the city of Surakarta in terms of acceptance, is a taxwhich has the greatest acceptance in post Surakarta local taxes. In addition, the usercommunity as a means of electricity can not be separated from their street lightingtax. The purpose of this study was to analyze the potential of street lighting taxrevenue in Surakarta. Analyze the effectiveness of street lighting tax revenue inSurakarta. Analyze the contribution of street lighting tax to the local tax inSurakarta. Data analysis technique used is quantitative descriptive analysis. Inconclusion that the potential tax revenue in Surakarta city street lighting from theyears 2011 – 2015 based on the analysis that in 2011 in the category of potential,whereas in the year 2012 to 2015 in the category of excellence. The effectiveness ofstreet lighting tax revenue in Surakarta from the years 2011 – 2015 is categorized asgood, average effectiveness of street lighting tax revenue that is equal to 105,10%.Street lighting tax contribution to the local tax in Surakarta from the years 2011-2015 that have fluctuating contribution. Against street lighting tax contribution oflocal tax in Surakarta from the years 2011 – 2015 on average amounted to 27,82%, ifit is based on criteria or indicators of assessment of contributions, the judgment inthe category of being.Keywords: potency, effectiveness, contribution, street lighting tax, local taxes.